Potential application of a newly isolated phage BUCT609 infecting Stenotrophomonas maltophilia - Han, Ke; Dong, Yuqi; An, Xiaoping; Song, Lihua; Li, Mengzhe; Fan, Huahao; Tong, Yigang (Frontiers in Microbiology, 2022)
Stenotrophomonas maltophilia (S. maltophilia) is widely distributed in nature and frequently causes nosocomial infections. In this work, the biological characteristics and genome of a new S. maltophilia phage BUCT609 isolated from hospital sewage with S. maltophilia strain No. 3015 as host was analyzed and its therapeutic effect in vivo was explored. It was observed by TEM that phage BUCT609 belongs to the Podoviridae with a 10 nm tail structure and a capsid with a diameter of about 50 nm. It has a short latent period (about 10 min) and its burst size is 382 PFU /cell when multiplicity of infection (MOI) is 0.01. Furthermore, it has a high survival rate in the environment with a pH range from 3 to 10 and temperature range from 4°C to 55°C. The complete genome of phage BUCT609 is linear double-stranded DNA of 43,145 bp in length, and the GC content is 58%. The genome sequence of phage BUCT609 shares <45% homology with other phages. No virulence genes and antibiotic resistance genes were found in bacteriophage BUCT609. In vivo animal experiments showed that the survival rate of mice infected with S. maltophilia was significantly improved after the intranasal injection of phage BUCT609. Therefore, our study supports that phage BUCT609 could be used as a promising antimicrobial candidate for treating S. maltophilia infections.